2018
DOI: 10.1111/acer.13608
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ethanol Inhibition of Adult Hippocampal Neurogenesis Involves CB1 Cannabinoid Receptor Signaling

Abstract: Together, these findings suggest that acute CB1R cannabinoid receptor activation and binge EtOH treatment reduce neurogenesis through mechanisms involving CB1R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Previous studies have also found that AIE exposure causes a persistent increase in hippocampal expression of proinflammatory Toll-like receptors (TLR), the proinflammatory cytokine TNF-α and high mobility group box 1 (HMGB1), as well as the transcriptionally active subunit phosphorylated (activated) NFκB (pNFκB p65) common to proinflammatory signaling 52,53 . The persistence of neuroimmune signaling after AIE may be related to the persistent increases in adult hippocampal HMGB1, which can activate TLR and the receptor for advanced glycation end-products (RAGE).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also found that AIE exposure causes a persistent increase in hippocampal expression of proinflammatory Toll-like receptors (TLR), the proinflammatory cytokine TNF-α and high mobility group box 1 (HMGB1), as well as the transcriptionally active subunit phosphorylated (activated) NFκB (pNFκB p65) common to proinflammatory signaling 52,53 . The persistence of neuroimmune signaling after AIE may be related to the persistent increases in adult hippocampal HMGB1, which can activate TLR and the receptor for advanced glycation end-products (RAGE).…”
Section: Resultsmentioning
confidence: 99%
“…In establishing novel rodent models of THC and alcohol co-use, we found that injected or orally administered THC can dose-dependently interact with alcohol to differently influence feeding behaviors. Importantly, our established method of voluntary THC and alcohol ingestion is an improvement over two recent involuntary coadministration models (Khatri et al 2018;Swartzwelder et al 2012), and closely recapitulates the manner of human consumption. Our methods can be easily adapted for investigations of the behavioral, metabolic, and neurobiological mechanisms of joint alcohol and cannabinoid use in adolescent and adult subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic alcohol exposure is known to inhibit adult hippocampal neurogenesis, and in this Virtual Issue, Khatri and colleagues used a rat binge‐drinking model to show that acute alcohol inhibition of neurogenesis depends on activation of CB1 receptors and is exacerbated by further activation of these receptors (Khatri et al., ). This model suggests that acute activation of endocannabinoid signaling by alcohol is an important step in impairment of hippocampal neurogenesis.…”
Section: Endocannabinoids Exocannabinoids and Alcohol Actionsmentioning
confidence: 99%